2008
DOI: 10.1007/s10611-008-9145-1
|View full text |Cite
|
Sign up to set email alerts
|

Measuring corporate environmental crime rates: progress and problems

Abstract: The problem of corporate crime rates has been the subject of debate, speculation and operationalization for decades, largely stemming from the complexity of measuring this type of crime. Examining corporate environmental crime poses challenges and creates opportunities for advancing the discussion of corporate crime rates, but criminologists are less familiar with environmental data. In the current paper, we review the strengths and weaknesses of existing environmental data that can be used to construct the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 3 publications
0
29
0
1
Order By: Relevance
“…Some researchers take a broader view to estimate the prevalence of environmental harm in the United States (Bullard et al, 2009), while others have utilized a variety of self-reported data and government databases to look at the prevalence and causes of environmental crime (Brickey, 2001;Lynch et al, 2004aLynch et al, , 2004bStretesky, 2006;Ozymy and Jarrell, 2012). Ultimately, there is simply a need for more data to properly empirically assess both the prevalence and prosecution of green crimes in the United States and abroad (Gibbs and Simpson, 2009). In this article, we follow the lead of scholars that utilize government databases to look at the prevalence of green crimes occurring across the United States, with a particular focus on federal environmental crime prosecutions occurring within and across the U.S. states, 2001-2011.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers take a broader view to estimate the prevalence of environmental harm in the United States (Bullard et al, 2009), while others have utilized a variety of self-reported data and government databases to look at the prevalence and causes of environmental crime (Brickey, 2001;Lynch et al, 2004aLynch et al, , 2004bStretesky, 2006;Ozymy and Jarrell, 2012). Ultimately, there is simply a need for more data to properly empirically assess both the prevalence and prosecution of green crimes in the United States and abroad (Gibbs and Simpson, 2009). In this article, we follow the lead of scholars that utilize government databases to look at the prevalence of green crimes occurring across the United States, with a particular focus on federal environmental crime prosecutions occurring within and across the U.S. states, 2001-2011.…”
Section: Discussionmentioning
confidence: 99%
“…While theorizing and describing the causes of green crime has been an early goal of green criminologists, describing the extent of green crimes locally or comparatively can be difficult, as there are no uniform or national statistics in the United States regarding the prevalence of environmental crimes (Gibbs and Simpson, 2009). Generally researchers develop databases or rely on estimates, based on governmental data or more limited data provided by non-governmental organizations.…”
mentioning
confidence: 99%
“…To date, the study of illegal waste activity has been constrained by data collection and data quality issues (Gibbs and Simpson, 2009). Most crime analysis (conducted in policing agencies) is conducted using information that is recorded in databases on crime incidents.…”
Section: Discussionmentioning
confidence: 99%
“…exporting and importing) are not subject to any pre-notification requirements, which means that the authorities are not consistently informed about this type of activity. However, illegal waste activity is a relatively new legal concept and subject of study (Gibbs and Simpson, 2009), so perhaps it is natural that it takes time for appropriate recording systems to emerge. For example, it has only been in the last 20 years that police agencies have systematically managed the recording of incidents of crime electronically, even though in some cases these agencies have existed for centuries (Ratcliffe, 2008).…”
Section: Data Recording and Qualitymentioning
confidence: 99%
“…Measuring environmental crime is complex [62] and it is difficult to assess [63]. Illegal transports of e-waste are no exception.…”
Section: The Scale Of Illegal Transports Of E-waste: Best Guesstimatementioning
confidence: 99%